FORMATION OF TEMPORARY COMPETENCE OF EDUCATION ACQUISITIONS IN THE CONDITIONS OF SOCIAL CHANGES - Zaiets , Nataliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article presents a study of the peculiarities of the formation of temporal competence of education seekers, which is due to the search for new approaches to the quality of training future specialists in the higher education system, taking into account social requirements and individual needs. The purpose of the study is to investigate the peculiarities of the formation of time competence of education seekers in the conditions of higher education institutions and to highlight the main provisions of successful professional time management of future specialists. The task of the research: to determine the original theoretical provisions regarding the formation of the temporal competence of the individual; to analyze the experience and peculiarities of the formation of temporal competence of education seekers; to determine the structural components and the role of the formation of temporal competence of education seekers in the conditions of higher education institutions. The following research methods were used to solve the outlined tasks: analysis of scientific literature; theoretical (analysis, synthesis), pedagogical observations. As a result of the study, it was proved that planning and perception of time in wartime conditions requires from the students the skills of quick and effective determination of time priorities, prompt adjustment of their own activities, regulation of their own time limits when solving educational or professional situations. The positive effect of the formation of temporal competence as a modern meta-competence (Soft Skills) consists in the ability to rationally and effectively organize professional activity and personal life in the temporal dimension.